Diagnóstico das famílias beneficiadas pelo programa de microcrédito rural (agroamigo) no estado do Ceará: Um estudo de caso - Maciel, Harine Matos (2009)
The main objective of this study was to make a diagnostic of the benefited families by rural small credit program in the state of Ceará. The primary data was obtained through the apliction of questionaires to benefited and non-benefited families, slected randomly in Quixadá municipality. The table, descriptive and grafic techniques were used to analyse the data. The t-Student, Tukey and Kruskall-Wallis tests were used to compare the mean values and proportions, respectively. A quallity life index was calculated to analyse the quality of life of benefited and non-benefited families. The results showed that the average age of beneficiaries is lower than that of non-beneficiaries and level of schooling of beneficiaries is higher when compared to non-beneficiaries. The main occupation of respondents is agriculture. The majority of interviewed farmers are owners of small farms and are using family labor. The labor use per cultivated hectare is higher in cattle and swine activities. The agriculture and pension and retirement, respectively is the main source of income of majority of benefited and non-benefited families. The highest average agricultural income per cultivated hectare is obtaineed in swine activity due to its faster financial returns as compared to cattle and sheep raising activities. The benefited and non-benefited families has average quality of life. The indicators like living conditions, education and health contributed more in the construction of quality life index, where as the indicator leisure has the lowest participation. The program facilitated the availability of credit to small farmers. It is necessary to monitor more strictly the utilization of credit resoources and to guide farmers in improving their performance in the market.